Understanding and Measuring Parent Use of Food to Soothe Infant and Toddler Distress: A Longitudinal Study from 6 to 18 months of age - Stifter, Cynthia A. (Appetite, 2015)
The present study examined the development of parent use of food to soothe infant distress by examining this feeding practice longitudinally when infants were 6, 12 and 18 months of age. Two measures of feeding to soothe were obtained: parent self-report and observations of food to soothe during each laboratory visit. Demographic and maternal predictors of food to soothe were examined as well as the outcome, infant weight gain. The findings showed that the two measures of food to soothe were unrelated but did reveal similar and unique relations with predictor variables such as parent feeding style and maternal self-efficacy. Only observations of the use of food to soothe were related to infant weight gain. The findings indicate that the two measures of food to soothe may be complementary and that observations of this feeding practice may capture certain relations that are not obtained through the use of self-report.